Pelaksanaan Uji Kompetensi Keahlian Siswa SMK Teknik dan Bisnis Sepeda Motor oleh LSP P1 di Jawa Barat - Mulyana, Tatang; Kamaludin, Muhamad; Setyadin, Asep S.; Saputro, Bambang Eko; Ayasrah, Firas Tayseer (Universitas Lampung, 2024)
This study aims to evaluate the implementation of the Vocational Competency Test (UKK) in the Motorcycle Engineering and Business (TBSM) program conducted by the Professional Certification Institute (LSP) P1 in West Java Province, focusing on the aspects of assessor qualifications and the adequacy of practical facilities. The study employed an evaluative method with a descriptive approach. The research subjects consisted of six vocational high schools (SMK) with TBSM programs that implemented the UKK through LSP P1 in 2022. The respondents, totaling 24 people, included assessors, LSP P1 chairpersons, and heads of Test Centers (TUK). Data were collected through questionnaires, observations, interviews, and documentation. Instrument validity was tested using content validity through expert judgment by vocational education and motorcycle engineering experts, while reliability was examined using the Cronbach’s Alpha coefficient. Data were analyzed descriptively using categorical level analysis. The results showed that the implementation of the TBSM UKK by LSP P1 in West Java was classified as very good, with achievement levels of 93% for assessor qualifications and 90% for practical facilities. However, some shortcomings were identified, particularly regarding assessor qualification standards and the adequacy of practice equipment. Overall, the UKK implementation has been effective, but improvements in assessor quality and practice facilities are needed to ensure more optimal and industry-aligned competency testing.Kata kunci: LSP P1, SMK, Teknik sepeda motor, Uji kompetensi